Innovative Tools for Business Coalitions in B2B Applications How Negotiation, Auction and Game Theory Can Support Small- and Medium-sized Business in E-business - Argoneto, Pierluigi; Renna, Paolo; SpringerLink (Online service) (London : Springer London, 2011)
The manufacturing industry is facing the challenges of shifting its operations from the traditional factory integration philosophy to a supply chain based e-factory philosophy, and of transforming the focus of companies from the local factory to global enterprise and business. Innovative Tools for Business Coalitions in B2B Applications presents a set of innovative methodologies that can be used to face all the issues that stem from the interaction of customers and suppliers in an e-marketplace environment. The first methodology discussed is multi-agent architecture and this forms the basis of a simulation environment developed in order to test the proposed models. The second concerns a bargaining model based on the negotiation mechanism and the third centers on production planning to support agents during the bargaining phase. The fourth is the possibility of a coalition between the suppliers and the authors offer a choice of two different approaches. One is the application of Nash equilibrium to select the members of a potential coalition of sellers, while the other is a centralized approach with a profit sharing mechanism based on the Shapley value. All the innovative approaches reported in Innovative Tools for Business Coalitions in B2B Applications have been statistically tested in different market conditions. The methodologies, approaches and results presented in Innovative Tools for Business Coalitions in B2B Applications will be of interest to PhD students, operations managers and supply chain management researchers who develop value-added services for an e-marketplace in a business-to-business environment.
1. Business to Business E-marketplaces: A Literature Overview and Motivations -- 2. Multi Agent Architecture -- 3. Game Theory Overview -- 4. Bargaining Models in E-marketplaces -- 5. Models for Coalition Management -- 6. Simulation Environment -- 7. Simulation Results -- 8. Conclusions and Future Developments.
Keywords: Engineering; Information systems; Engineering economy; Economics, Mathematical; Business planning; Engineering; Engineering Economics, Organization, Logistics, Marketing; Organization/Planning.; Game Theory/Mathematical Methods; Information Systems Applications (incl.Internet).